Guide to software development : designing and managing the life cycle - Langer, Arthur M. (Springer, 2012)
Offering an integrated approach that includes important management and decision-making practices, this book shows how to create successful solutions that closely fit user and customer needs, by blending software development life cycle (SDLC) methodologies